The bright side of microbial dark matter: lessons learned from the uncultivated majority. (June 2016) - Solden, Lindsey; Lloyd, Karen; Wrighton, Kelly
Graphical abstract: Highlights: Recent discoveries from metagenomics and single cell genomics. Metabolic features of the uncultivated majority. Success stories of cultivating microbial dark matter. Abstract : Microorganisms are the most diverse and abundant life forms on Earth. Yet, in many environments, only 0.1–1% of them have been cultivated greatly hindering our understanding of the microbial world. However, today cultivation is no longer a requirement for gaining access to information from the uncultivated majority. New genomic information from metagenomics and single cell genomics has provided insights into microbial metabolic cooperation and dependence, generating new avenues for cultivation efforts. Here we summarize recent advances from uncultivated phyla and discuss how this knowledge has influenced our understanding of the topology of the tree of life and metabolic diversity.